The Effect Of Principal Supervision On Teacher Performance Improvement - Amirul Hidayat (Eduvest - Journal of Universal Studies, 2021)
The goals to be achieved from a principal's supervision are goals that are in accordance with predetermined standards. Therefore, to ensure the quality of teaching and learning services or good teacher performance, the supervision of the principal is important in providing guidance, guidance and supervision to teachers. This supervision and improvement is something that must be highlighted to become a benchmark for improving the teaching and learning process that will result in good quality education. The research used quantitative method research was carried out for 3 months starting from September to November 2019. The place that became the research center was at SDS IT Al Fajar Sungai Pakning. The subject in this study was the principal while the object in the study was the teacher at SDS IT Al Fajar. The population in this study were principals and teachers. The samples taken by the researchers were SDS IT teachers, Al Fajar Sungai Pakning, totaling 35 people. After the authors conducted data management through questionnaires and analyzed the data, it can be concluded that the supervision of the principal at Sds It Al Fajar Sungai Pakning was categorized as "good" with a percentage value of "100%.